Rancang Bangun Alat Pemantau Suhu Kandang Ayam dan Stok Pakan Menggunakan Arduino Nano Berbasis SMS Gateway - Eko Ardyansyah; Yoga Listi Prambodo; Asruddin Asruddin (FIKOM Universitas Bung Karno, 2023)
This research focuses on the development of a temperature monitoring device for chicken coops and chicken feed, which is essential in the poultry industry. The device is designed to address specific conditions in the livestock industry that cannot be manually handled by humans. The design methodology involves software development using object modeling (UML), hardware design through circuit schematics, and the construction of the device. The device utilizes HC-SR04 ultrasonic sensor and DHT11 sensor to measure humidity and temperature inside the chicken coop. Testing is conducted to measure the chicken feed supply using the ultrasonic sensor, as well as the humidity and temperature inside the chicken coop using the DHT11 sensor. The final outcome of this research is the implementation of a temperature monitoring device for chicken coops and chicken feed that functions according to the needs of poultry farmers. The Arduino Nano microcontroller is integrated with an SMS gateway device as an intermediary to transmit programmed process instructions as text messages containing real-time information.